The influence of individual factors on hospitality students' internship satisfaction: The mediation role of perceived importance - Irene Hanna H. Sihombing (Global Business & Finance Review (GBFR), 2021)
Purpose: This study explains the effect of academic preparedness, positive attitude, and self-initiative towards satisfaction in students' industrial training (internship) program. Those three independent variables are dimensions of individual factors variable, while individual factors variable is one of the determinants of training effectiveness. The purpose of the study is to explain the individual factors and the role of perceived importance that mediates the relationship of the respective individual factor to the internship satisfaction. Design/methodology/approach: The research population was the 6th and 8th semester students of Diploma IV Hospitality Administration of Bali Tourism Polytechnic. Students of the Diploma IV Hospitality Administration study program at Bali Tourism Polytechnic performed an internship program twice, with a duration of 6 months respectively. Respondents who returned and filled out the questionnaire correctly were 178 respondents. The hypotheses and the research model were analyzed by using the Structural Equation Model (SEM) with a PLS basis. Findings: The research findings are (1) individual factors bring positive and significant effect towards internship job satisfaction, (2) individual factors have positive and significant effect towards perceived importance, (3) perceived importance has positive and significant effect towards job satisfaction, and (4) perceived importance influenced individual factors in job satisfaction. Research limitations/implications: This study was conducted to improve the individual factors of the hospitality students to enhance their skills in the real working condition. For future related study, it is demanded to investigate the impact of the industrial training for the students' decision in continuing to pursue their career in the hospitality industry. Originality/value: In general, this research can contribute to empirical literature concerning on the perception of vocational students' industrial training. Furthermore, this study contributes to Bali Tourism Polytechnic in developing the industrial training program for the students and preparing the vocational students to be ready in the hospitality industry.
Keywords: 650; individual factor; job satisfaction; perceived importance; vocational education; hospitality